Prove that 1*1! + 2*2! + 3*3!+...+ n*n!= (n+1)!-1 whenever n is a positive integer.
Ive been stuck for a bit on it. Thanks
There's a nice little introduction to proofs by induction from the University of Sydney that you can find here:
http://sydney.edu.au/stuserv/documents/maths_learning_centre/induction.pdf
Here are a few little hints to get you started:
Since you're dealing with all the positive integers, you want to start off by thinking about what happens when n = 1. Is your proposition true?
Then, the basic strategy is to show that if it's true for
n = 1 then it must be true for
n = 2, and if it's true for
n = 2 then it must be true for
n = 3, etc. This can be accomplished by showing that if it's true for
n = some positive integer
k, then it must also be true for the next largest positive integer
n =
k+1).
By doing this you will have proved that it must be true for every positive integer.
I hope that helps you get started. See what you can come up with!